KAJIAN SEMIOTIKA SEBAGAI STRATEGI KOMUNIKASI PADA FILM ENSLAVED - Tirta Yasa, Desak Putu Yogi Antari (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Film semiotics is one of the main field on film theory which is important to understand as a paradigm in the process of film study and creation. A specific study about film semotics is needed, one of it by reviewing film that apply film semiotics as communication strategy. Enslaved is a film by Yayasan Seva Bhuana and Sanggar Sri Redjeki Films which is interesting to be studied because it applied film semiotics as communication strategy. The method used in this research is qualitative method by the determination of research subject, research object, research location, research design, informants, methods of collecting data and methods of data processing. The analysis methods used in this research is semiotics methods which is qualitative-interpretative and empiric semiotics methods with descriptive-analitive methods on data presentation. The result of this research is a study of the application of film semiotics theory and how semiotics elements related to the film elements in Enslaved.